Mathematical modeling of lipid peroxidation reactions of vegetable oil with phytochemical antioxidant treatment during frying. - Jaswir, Irwandi (2009)
Antioxidants are important inhibitory materials against the oxidative deterioration of food. The present study focused on the effect of various phytochemical antioxidant systems [oleoresin rosemary (OR), oleoresin sage (OS) and citric acid (CA)] on the changes in physico-chemical characteristics of refined-bleached-deodorized (RBD) palm olein. The oxidative behavior of various mixtures of these antioxidants in RBD palm olein was also conducted during repeated deep-fat frying. Response surface methodology was used to optimize the use of the mixtures. A comparative study was carried out with the use of synthetic antioxidants. Fried oil samples were analyzed for different physical and chemical properties. Results showed that OR and SE were two effective phytochemical antioxidants for the protection of RBD palm olein against oxidative deterioration during frying